Chuva de sementes e regeneração natural em áreas de Cabruca na região cacaueira do Norte do Espírito Santo, Brasil - Vieira, Paula Bastos (2014)
In the Espirito Santo State, the most part of cocoa plantations was implanted in the Atlantic forest thinned in a system known as cabruca, which spans for 18 acres along the banks of the Rio Doce, in Linhares. Given the importance of the plantation system in the region and through the premise that management implemented this type of cultivation is committed to conserving the diversity of the northern forests of Espirito Santo state, we sought to verify the difference between the tree community that comes through seed rain and that settles on cabrucas regeneration under different management conditions. To this have been selected three areas of study and the present study was divided into two chapters. The first is an analysis of the seed rain in an area of cabruca activity. 30 seed collectors with circular aperture equal to 0.19625 m2, 157 cm in circumference and 50 cm in diameter and 13 m distant from each other were installed. The material deposited on them was collected monthly for fifteen months. The second chapter consists of a review of the structure of the vegetation that is established through natural regeneration in two areas adjacent cabrucas, one with seven and one with fifteen years of abandonment about. 25 plots of 5 x 5m, two meters distant from each other were demarcated in each area abandoned. All individuals larger than 30 cm and DAS (diameter at ground height) Maximum height of 10 cm were sampled and a better understanding of the structure regenerating individuals were separated into three size classes. The assessment of the degree of similarity between the three communities was performed with multivariate statistical test known as Procrustes. To test whether species richness differed among the three communities used the univariate called randomization Orlóci & Pillar (1996) test. In the study 192 species were detected in the three areas assessed. These are distributed in 97 genera and 47 families. In general, the correlations for the three areas assessed correlations are low,and are only significant between the area where they evaluated the seed